Neuropsychiatric symptoms and intelligence quotient in autosomal dominant Segawa disease - López-Laso, Eduardo; Sánchez-Raya, Araceli; Moriana, Juan Antonio; Martínez-Gual, Eduardo; Camino-León, Rafael; Mateos-González, María Elena; Pérez-Navero, Juan Luis; Ochoa-Sepúlveda, Juan José; Ormazabal, Aida; Opladen, Thomas; Klein, Christine; Lao-Villadóniga, José Ignacio; et al. (Journal of neurology, 2011)
Segawa disease is a rare dystonia due to autosomal dominant guanosine triphosphate cyclohydrolase I (adGTPCH) deficiency, affecting dopamine and serotonin biosynthesis. Recently, the clinical phenotype was expanded to include psychiatric manifestations, such as depression, anxiety, obsessive-compulsive disorder, and sleep disturbances. Although cognitive and neuropsychiatric symptoms may be attributable to dopamine deficiency in the prefrontal cortex and frontostriatal circuitry, intelligence is considered normal in Segawa disease. Our aim was to investigate neuropsychiatric symptoms and intelligence quotients (IQ) in a series of individuals with adGTPCH deficiency. The assessment included a structured clinical interview following the DSM-IV-TR’s guidelines, Beck’s Depression Inventory, the State-Trait Anxiety Inventory, the Maudsley Obsessive-Compulsive Questionnaire, the Barratt Impulsiveness Scale-11 (BIS-11), the Oviedo Sleep Questionnaire, the Pittsburgh Sleep Quality Index, and the Wechsler Adult Intelligence Scale-Third Edition. Equivalent tests were applied to pediatric patients as appropriate for their age group. Fourteen patients with adGTPCH deficiency were evaluated (seven adult and seven pediatric patients). Depression, anxiety, and obsessive-compulsive symptoms were not more common than expected in the general population. However, the seven adults showed impulsivity in the BIS-11; nine individuals had an IQ in the range of borderline intellectual functioning to mild mental retardation, and sleep disturbances were found in four individuals. We found no differences between these results and the motor impairment. In conclusion, our findings would suggest that cognitive impairment, and impulsivity in adults, may be associated with Segawa disease.